Effects of Combined Physical and Cognitive Virtual Reality-Based Training on Cognitive Impairment and Oxidative Stress in MCI Patients: A Pilot Study - Mrakic-Sposta, Simona; Di Santo, Simona G.; Franchini, Flaminia; Arlati, Sara; Zangiacomi, Andrea; Greci, Luca; Moretti, Sarah; Jesuthasan, Nithiya; Marzorati, Mauro; Rizzo, Giovanna; Sacco, Marco; Vezzoli, Alessandra (Frontiers in Aging Neuroscience, 2018)
The growing elderly population and the increased incidence of mild cognitive impairment (MCI) and Alzheimer’s disease (AD) call for the improvement of the quality and the efficacy of the healthcare and social support services. Exercise and cognitive stimulation have been demonstrated to mitigate cognitive impairment and oxidative stress (OxS) has been recognized as a factor that contributes to the advancement of neurodegenerative diseases. Taking these aspects into account, the impact of a novel virtual reality (VR)-based program combining aerobic exercise and cognitive training has been evaluated in the pilot study proposed here. Ten patients (aged 73.3 ± 5.7 years) with MCI (Mini-Mental State Examination, MMSE: 23.0 ± 3.4) were randomly assigned to either 6 weeks physical and cognitive training (EXP) or control (CTR) group. Evaluations of cognitive profile, by a neuropsychological tests battery, and OxS, by collection of blood and urine samples, were performed before and at the end of the experimental period. The assessment of the patients’ opinions toward the intervention was investigated through questionnaires. EXP group showed a tendency towards improvements in the MMSE, in visual-constructive test and visuo-spatial tests of attention, while CTR worsened. EXP group showed a greater improvement than CTR in the executive test, memory functions and verbal fluency. No statistical significance was obtained when comparing within and between both the groups, probably due to small number of subjects examined, which amplifies the effect of the slight heterogeneity in scores recorded. Despite a greater worsening of Daily Living Activities tests, all participants reported a better performance in real life, thanks to the elicited self-perceived improvement. After training intervention OxS (i.e., reactive oxygen species (ROS) production, oxidative damage of lipids and DNA) decreased resulting in significantly (range p < 0.05–0.001) lower in EXP vs. CTR group. Although not conclusive, the recorded effects in the present study are promising and suggest that this proposal would be a useful tool in support of cognitive training reducing OxS too. However, further studies on larger scale samples of patients are needed.